Analisis Strategi Komunikasi Saka Tarunabumi dalam Regenerasi Petani di Kota Semarang - Kresna, Nabila; Satriya, Candra (Jurnal KIRANA, 2025)
The aging of farmers is a significant challenge for the agricultural sector in Indonesia, which plays an important role in sustainable development and food security. In the city of Semarang, the number of millennial farmers is still very low, even though the city is striving to achieve food security through modern agriculture and urban farming. This study aims to analyze the communication strategies implemented by the Semarang City Agriculture Department through the Saka Tarunabumi program in regenerating young farmers. Using a descriptive qualitative approach and case study method, this research involves the Head of the Extension Division of the Agriculture Department, the Chair of Saka Tarunabumi, active members, and young farmers as informants. Primary data was obtained through observation and interviews, supplemented by secondary data from relevant documents. Data analysis was conducted using the interactive Miles and Huberman model, along with data source triangulation to ensure validity. The study findings indicate that the Semarang City Agriculture Department implements three main communication strategies (foundation, application, and implementation) based on the Holtzhausen. At the foundation stage, the instillation of the organization's vision, mission, and values successfully created a sense of ownership and enthusiasm among members. The application stage involved identifying issues through SWOT analysis and setting goals to cultivate a young generation passionate about agriculture. The implementation stage focused on program execution, collaboration with external parties, and the application of a participatory two-way communication approach. Regular training, demonstration plot planting programs, and the use of Instagram as a social media platform are key elements, although there is room for improvement in optimizing Instagram. This communication strategy has proven effective in increasing young people's interest and skills in agriculture, as well as contributing to efforts to regenerate farmers in the city of Semarang.